TINGKAT PELAYANAN KINERJA KARYAWAN TERHADAP ANALISIS KEPUASAN KONSUMEN DENGAN METODE IMPORTANCE PERFORMANCE ANALYSIS - Wimbawani, Wiwik (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
In analyzing employee performance service levels on customer satisfaction in Indomaret Yos Sudarso Metro Pusat. using the Importance Performance Analysis (IPA) method and Customer Satisfaction Index (CSI). The aim of this research is to evaluate effectiveness of services provided by employees and understanding customer satisfaction obtained from the store atmosphere aspect. Data was collected through distributed questionnaires to Indomaret Yos Sudarso Metro Pusat customers and analyzed quantitatively. Results analysis shows that store atmosphere elements such as interior displays, store layout, general interior and store exterior have a significant influence on customer satisfaction. Several indicators that fall into the top priority category require improvement performance, while indicators in the maintain achievement category show good performance adequate and needs to be maintained. This study provides recommendations for management Indomaret to focus on improving the quality of elements deemed important by customers to increase overall customer satisfaction and loyalty.